2005
DOI: 10.1111/j.1471-4159.2005.03102.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐amyloid peptides stimulate endozepine biosynthesis in cultured rat astrocytes

Abstract: Accumulation of b-amyloid peptide (Ab), which is a landmark of Alzheimer's disease, may alter astrocyte functions before any visible symptoms of the disease occur. Here, we examined the effects of Ab on biosynthesis and release of diazepam-binding inhibitor (DBI) There is now clear evidence that, in the brain, the DBI gene is primarily expressed in glial cells (Tong et al. 1991;Lihrmann et al. 1994;Alho et al. 1995;Bürgi et al. 1999) and the presence of DBI-related peptides has been visualized by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
(118 reference statements)
3
15
0
Order By: Relevance
“…The concentration of endozepines is elevated in the cerebral spinal fluid of patients with Alzheimer's and Parkinson's diseases [60] and it has been reported that β-amyloid peptide, the major constituent of senile plaques, induces endozepine biosynthesis and release from cultured astrocytes [61], [62]. Moreover, ODN exerts a proliferative effect on some cell types, notably astroglial cells [35], [62], suggesting that over-production of ODN may contribute to astrocyte proliferation observed in various neurodegenerative diseases. Besides, the present data indicate that ODN prevents H 2 O 2 -induced astrocyte apoptosis which is in agreement with a study showing that DBI silencing with siRNA leads to growth arrest and apoptosis in various mammalian cell lines [63].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of endozepines is elevated in the cerebral spinal fluid of patients with Alzheimer's and Parkinson's diseases [60] and it has been reported that β-amyloid peptide, the major constituent of senile plaques, induces endozepine biosynthesis and release from cultured astrocytes [61], [62]. Moreover, ODN exerts a proliferative effect on some cell types, notably astroglial cells [35], [62], suggesting that over-production of ODN may contribute to astrocyte proliferation observed in various neurodegenerative diseases. Besides, the present data indicate that ODN prevents H 2 O 2 -induced astrocyte apoptosis which is in agreement with a study showing that DBI silencing with siRNA leads to growth arrest and apoptosis in various mammalian cell lines [63].…”
Section: Discussionmentioning
confidence: 99%
“…2008). We have recently found that the endozepine ODN induces a concentration‐dependent increase of the number of astrocytes in primary culture (Tokay et al. 2005), suggesting that ODN may be involved in the control of survival or/and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…1990). We have recently shown that β‐amyloid peptide induces activation of endozepine biosynthesis and release, suggesting that over production of ODN may contribute to astrocyte proliferation associated with AD (Tokay et al. 2005, 2008).…”
mentioning
confidence: 99%
“…1993). Stimulation of cultured astrocytes by either β‐amyloid peptides or pituitary adenylate cyclase activating polypeptide evokes expression and secretion of ACBP (Tokay et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1999). Treatment of astrocytes with β‐amyloid peptides not only induces secretion of ACBP (Tokay et al. 2005) it also increases intracellular calcium (Jalonen et al.…”
Section: Discussionmentioning
confidence: 99%